Budaya Sekolah di SMK Negeri Se-Kota Padang - Pranata, Fauzi Dwi; Gistituati, Nurhizrah (Lembaga Yasin AlSys, 2024)
School culture is a social behavior that is not visible but greatly influences the success of the school in achieving its goals by using indicators of a culture of collective efficacy (Collective Efficacy Culture), a culture of trust in schools, a culture of academic optimism (Academic Optomism), and a culture of control and humanism (Costudial -Humanistic Culture). This type of research is quantitative descriptive research. The population in this research is all teachers in State Vocational Schools throughout Padang City totaling 818 teachers with a research sample of 135 teachers who will be taken based on the Stratified Proportional Random Sampling technique. The instrument used was a Likert scale model questionnaire. The questionnaire was tested for validity and reliability assisted by the SPSS program. The data analysis technique uses the Average Mean formula. The research results show that school culture in terms of aspects: 1) the culture of collective efficacy is in the good criteria, getting an average score of 4.32 with TCR (86.34%), 2) the culture of trust in the school is in the good criteria, getting an average score. 4.34 with TCR (86.78%), 3) the culture of academic optimism is in the good criteria getting an average score of 4.39 with the TCR (87.82%), 4) the culture of control and humanism is in the good criteria getting a score average 4.42 with TCR (88.37%). Thus, it was concluded that the school culture in State Vocational Schools throughout Padang City was in good criteria, obtaining an average score of 4.36 with TCR (87.32%).